Neurogenic Edema from Complex Regional Pain Syndrome Resulting in Fulminant Infection Necessitating Below Elbow Amputation - Carpenter, Daniel P.; Draeger, Reid W. (Journal of Hand and Microsurgery, 2017)
We report a case of severe upper extremity complex regional pain syndrome type 1 (CRPS-1) and neurogenic edema that ultimately led to a medically necessary below-elbow amputation. The patient presented with a history of remote bilateral carpal tunnel release complicated by debilitating and recalcitrant bilateral CRPS-1. Following years of severe neurogenic edema of the left upper extremity, the patient had full-thickness skin sloughing on the dorsum of her hand due to massive edema. This subsequently led to maggot infestation of the soft tissues of the left hand ultimately necessitating amputation. We present the case as an illustration of an extreme case of neurogenic edema, a potential physical manifestation of CRPS-1. The case presented discusses upper extremity amputation as an end treatment option for CRPS-1, though in this case amputation was primarily indicated secondary to medical necessity.
Keywords: amputation; carpal tunnel syndrome; complex regional pain syndrome; infection; neurogenic edema